Skin sodium accumulates in psoriasis and reflects disease severity - Maifeld, András; Wild, Johannes; Karlsen, Tine V.; Rakova, Natalia; Wistorf, Elisa; Linz, Peter; Jung, Rebecca; Birukov, Anna; Gimenez-Rivera, Vladimir-Andrey; Wilck, Nicola; Bartolomaeus, Theda; Dechend, Ralf; et al. (The journal of investigative dermatology, 2022)
Sodium can accumulate in the skin at concentrations exceeding serum levels. A high sodium environment can lead to pathogenic T helper 17 cell expansion. Psoriasis is a chronic inflammatory skin disease in which IL-17‒producing T helper 17 cells play a crucial role. In an observational study, we measured skin sodium content in patients with psoriasis and in age-matched healthy controls by Sodium-23 magnetic resonance imaging. Patients with PASI > 5 showed significantly higher sodium and water content in the skin but not in other tissues than those with lower PASI or healthy controls. Skin sodium concentrations measured by Sodium-23 spectroscopy or by atomic absorption spectrometry in ashed-skin biopsies verified the findings with Sodium-23 magnetic resonance imaging. In vitro T helper 17 cell differentiation of naive CD4+ cells from patients with psoriasis markedly induced IL-17A expression under increased sodium chloride concentrations. The imiquimod-induced psoriasis mouse model replicated the human findings. Extracellular tracer Chromium-51-EDTA measurements in imiquimod- and sham-treated skin showed similar extracellular volumes, rendering excessive water of intracellular origin. Chronic genetic IL-17A‒driven psoriasis mouse models underlined the role of IL-17A in dermal sodium accumulation and inflammation. Our data describe skin sodium as a pathophysiological feature of psoriasis, which could open new avenues for its treatment.